Fear and disgust: case report of two uncommon emotional disturbances evoked by visual disperceptions after a right temporal-insular stroke - Mariagiovanna Cantone; Giuseppe Lanza; Rita Bella; Giovanni Pennisi; Paola Santalucia; Placido Bramanti; Manuela Pennisi (BMC Neurology, 2019)
Abstract Background Emotional processes and responses are underestimated in stroke patients because the massive clinical picture of large hemispheric strokes often hides these symptoms. We report on a patient with peculiar unpleasant emotional responses after temporal stroke. Case presentation We describe a 62-years old man with significant unpleasant emotional responses that occurred after an acute episode of confusional state, disorientation, agitation, vertigo, postural instability, vomiting, and photophobia. Since then, he complained that vision of pictures containing curved/multicolored lines or tangles was associated with an uncomfortable feeling of fear and disgust, lasting few minutes, so that he avoided looking at them. Notably, he also showed an abnormal facial expression of disgust and fear, together with neurovegetative reaction and horripilation, at the presentation of pictures of objects or animals containing curved, multicolored, or tangled lines. A post-acute infarction of the right temporal-insular region, together with mild periventricular white matter changes, were evident at the brain magnetic resonance imaging. Conclusions The anterior insula is crucial in transforming unpleasant sensory input into visceromotor reactions and the accompanying feeling of disgust. It is also known that temporal pole modulates visceral emotional functions in response to emotionally evocative perceptual stimuli. In the present case, the ischemic lesion of anterior part of the insula and temporal pole may have caused a decoupling of emotional and visceral response to complex visual stimuli. Further reports will provide a significant contribution to the taxonomy of these complex and relatively uncommon non-motor post-stroke symptoms that negatively affect quality of life.